1999
DOI: 10.1063/1.370150
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation mediated surface morphology of GaN

Abstract: The surfaces of GaN films grown by metalorganic chemical vapor deposition (MOCVD) and molecular beam epitaxy (MBE) were studied using atomic force microscopy (AFM). Due to the high dislocation densities in the films (108 cm−2), the typical surface morphologies of layers grown by both techniques were dominated by three dislocation mediated surface structures—pinned steps, spiral hillocks, and surface depressions. The characteristics of these surface structures were found to depend on growth technique (MOCVD vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
262
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(290 citation statements)
references
References 14 publications
26
262
0
2
Order By: Relevance
“…The depth of depressions varies from 2 to 6 nm. Studies of MOCVD-grown GaN films have found similar surface depressions and attribute them to the dislocations intersecting the surface [1,9]. For the sample here, it is likely that those surface depression valleys are filled with metallic Ga before annealing, as observed by Hsu et al [14].…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The depth of depressions varies from 2 to 6 nm. Studies of MOCVD-grown GaN films have found similar surface depressions and attribute them to the dislocations intersecting the surface [1,9]. For the sample here, it is likely that those surface depression valleys are filled with metallic Ga before annealing, as observed by Hsu et al [14].…”
Section: Resultssupporting
confidence: 72%
“…Subsequent annealing of this step-bunched surface produces small surface depressions, similar to those commonly reported for the MOCVD GaN and associated with dislocations intersecting the surface [1,9].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although the possible presence of TDs in (multi-)functional ternary-oxide thin films and heterostructures has been reported [6][7][8][9][10], details on their origin, role, and particularly avoidance, are not sufficiently understood.…”
Section: Threading Dislocations In Epitaxial Ferroelectricmentioning
confidence: 99%
“…When the flux further increases to a coverage of 2.44ML [ Fig. 2(e)], corresponding to the Ga bilayer structure, due to the existence of mixed-type dislocations, the stepped terraces show typical MBE-growth of spiral hillocks [14]. Finally, when the coverage exceeds the bilayer coverage, since small nano-islands consisted of Ga clusters are formed, Ga-droplet conditions are reached [ Fig.…”
Section: Resultsmentioning
confidence: 99%